Alternative rational technique to compute multi-objective linear programming problems - Abbas Younis al-Bayati; Basim Abbas Hassan; Baraat sulayman (al-Tarbiyah wa-al-ʻilm lil-ʻulūm al-insānīyah : majallah ʻilmīyah muḥakkamah taṣduru ʻan Kullīyat al-Tarbiyah lil-ʻUlūm al-Insānīyah fī Jāmiʻat al-Mawṣil, 2012)
Abstract In this paper, we have been suggested an alterative rational technique to compute the value of the objective function of a multi-objective linear programming problems. Numerical results indicate that the efficiency of our proposed technique corresponding to standard Chandra Sen method is very effective according to a number of selected test problems.